d-Tubocurarine and Berbamine: Alkaloids That Are Permeant Blockers of the Hair Cell's Mechano-Electrical Transducer Channel and Protect from Aminoglycoside Toxicity - Kirkwood, Nerissa K.; O'Reilly, Molly; Derudas, Marco; Kenyon, Emma J.; Huckvale, Rosemary; van Netten, Sietse M.; Ward, Simon E.; Richardson, Guy P.; Kros, Corné J. (Frontiers in Cellular Neuroscience, 2017)
Aminoglycoside antibiotics are widely used for the treatment of life-threatening bacterial infections, but cause permanent hearing loss in a substantial proportion of treated patients. The sensory hair cells of the inner ear are damaged following entry of these antibiotics via the mechano-electrical transducer channels (MET) located at the tips of the hair cell’s stereocilia. d-Tubocurarine (dTC) is a MET channel blocker that reduces the loading of gentamicin-Texas Red (GTTR) into rat cochlear hair cells and protects them from gentamicin treatment. Berbamine is a structurally related alkaloid that reduces GTTR labelling of zebrafish lateral-line hair cells and protects them from aminoglycoside-induced cell death. Both compounds are thought to compete with aminoglycosides for entry into hair cells through the MET channels. Here we show that dTC (≥6.25 µM) or berbamine (≥1.55 µM) protect zebrafish hair cells in vivo from neomycin (6.25 µM, 1h). Protection of zebrafish hair cells against gentamicin (10 µM, 6h) was provided by ≥25 µM dTC or ≥12.5 µM berbamine. Hair cells in mouse cochlear cultures are protected from longer-term exposure to gentamicin (5 µM, 48h) by 20 µM berbamine or 25 µM dTC. Berbamine is, however, highly toxic to mouse cochlear hair cells at higher concentrations (≥30 µM) whilst dTC is not. The absence of toxicity in the zebrafish assays prompts caution in extrapolating results from zebrafish neuromasts to mammalian cochlear hair cells. MET current recordings from mouse outer hair cells show that both compounds are permeant open-channel blockers, rapidly and reversibly blocking the MET channel with half-blocking concentrations of 2.2 µM (dTC) and 2.8 µM (berbamine) in the presence of 1.3 mM Ca2+ at -104 mV. Berbamine, but not dTC, also blocks the hair cell’s basolateral K+ current, IK,neo, and modelling studies indicate that berbamine permeates the MET channel more readily than dTC. These studies reveal key properties of MET-channel blockers required for the future design of successful otoprotectants.